The Effect of Implementing Narrative Empty Chair Relaxation Therapy (NECRT) on Aggressive Behavior in Physically Abused Children at Sentra Handayani Jakarta - Nada Al Ghani, Tasya Falihatul; Mildawati , Milly; Yuliani, Dwi (West Science Social and Humanities Studies, 2025)
Narrative Empty Chair Relaxation Therapy (NECRT) is an innovative psychosocial intervention that integrates the empty chair technique with relaxation methods, specifically guided imagery and deep breathing exercises, supported by narrative guidance appropriate for children. NECRT aims to address aggressive behavior in children who have experienced physical abuse, often rooted in unresolved emotional trauma. This therapy is designed to help clients explore emotions, develop empathy, and foster self-reflection, enabling them to understand the consequences of their actions, reduce defensive mechanisms, and develop healthy conflict resolution skills. This study employed a quantitative approach using a Single Subject Reversal Design (A-B-A). The participants included MRA, ZN, and RA, with observations focusing on verbal and non verbal manifestations of aggressive behavior. The validity of the measurement instruments was assessed using the percent agreement method, and data analysis was conducted through visual inspection within and across conditions.The findings demonstrated that NECRT effectively reduced aggressive behaviors, showing a positive trend in behavior improvement and a maximum overlap percentage between conditions of 28.57%.